Connecting the morphological and molecular species concepts to facilitate species identification within the genus Fragilaria (Bacillariophyta). Issue 4 (28th June 2019) - Kahlert, Maria; Kelly, Martyn G.; Mann, David G.; Rimet, Frédéric; Sato, Shinya; Bouchez, Agnès; Keck, François
Abstract : This paper explores the diversity and taxonomy of species within Fragilaria sensu stricto, an abundant and ecologically important diatom genus, taking advantage of cultured and DNA‐barcoded material. The goal is to facilitate the identification of European taxa within this complex, providing a unified view on morphological and molecular diversity. There is a general agreement that the separation of species within the group of Fragilaria is difficult because morphological descriptions of species are not consistent between authorities, ongoing taxonomic revisions have resulted in species described with standards of the late 20th and 21st centuries alongside descriptions based on 19th century (light microscopical) criteria, and because not all diagnostic characters can be seen in all specimens encountered in routine analyses. Consequent confusion could blur potentially important ecological distinctions between species. Our study demonstrated that some species defined on morphological criteria could be confirmed using the rbc L chloroplast gene as a genetic marker, for example, Fragilaria gracilis, Fragilaria tenera, Fragilaria perminuta, and Fragilaria subconstricta . However, even for those species, preliminary identifications based on morphology often differed from identifications based on phylogenetic clustering combined with detailed morphological study. Clades were well‐defined by rbc L, but based on morphology, the terminal taxa of these clades did not match the currently described Fragilaria species. To clarify recognition of these taxa, we describe three new species: Fragilaria agnesiae, Fragilaria heatherae, and Fragilaria joachimii .